STUDY OF WOODEN PILLAR FOUNDATION STRUCTURE IN STILT HOUSES ON THE COAST OF BANYUWANGI BEACH: KAJIAN STRUKTUR PONDASI TIANG KAYU PADA RUMAH PANGGUNG DI PESISIR PANTAI BANYUWANGI - Sunarko; HARI PRANOTO; mahfud (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to determine the Structure of Wooden Pillar Foundations on Stilt Houses on the Coast of Banyuwangi Beach The method used in the discussion is in the form of descriptive analysis, namely analyzing the data of the study object based on theories related to the topic and object of observation, with the aim of finding the system and form of construction applied to the foundation of the house in this village in accordance with three zones, namely waters, transition, and land. The final results conclude about the shape of the structure system and the construction of residential foundations in each zone of the region. The foundations of the houses in each zone show that on the land the house uses a foundation of a pillar, in transition with a pair of stones, and in the waters using a pair of stones and some directly with the pillars.